(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3bGSGf s)
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3GdfHJ hgh Gdbdjd GdeJaQb heG Hbi ef eGdg GdCYfGU hHbjJ ai QCSg YfGU EPG Hbi ai QCSg TYQ eJaQb s
(3BNQgG (B:s
(3GdGjG GSdei jG OGQei Ydi GdHdi hdG RGd efgdkG HLQYGFc GdbWQ s
(3GdfSNI HgG MhGTs
(3fbdJ Yf fSNI cJHJ SfI (B596 (3HbGSGf CjVkGs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs